KAJIAN PENGERINGAN BUAH PINANG BELAH MENGGUNAKAN MESIN PENGERING TIPE ROTARI DENGAN SUMBER PANAS DARI API KOMPOR BERBAHAN BAKAR OLI BEKAS - Syahrizal, Iman; Ningsih, Irma Fahrizal Butsi (PPPM POLTESA, 2023)
This study aims to determine the results of drying betel nut split using a rotary type of drying machine with a heat source from the stove fire. The dependent variables in this study consisted of the time period of change in drying phase, drying rate, weight loss, texture change and betel nut color change resulting from the drying process. The method applied in this study was an experiment by paying attention to two main factors that can affect the drying process, namely the temperature and flow rate of air exhaled into the drying chamber. The reduction in fruit weight from the drying process was calculated based on the initial weight subtracted by the final weight after drying. The results showed that the drying of areca nut underwent three phases consisting of the initial adjustment phase that occurred in the drying time period of the 1st hour to the 3rd hour with a maximum drying rate of 0.8 kg / hour, the constant rate phase that occurred in the drying time period of the 3rd hour to the 4th hour with a drying rate of 1 kg / hour, and the declining phase that occurs in the 4th to 10th hour rigging time period with an average drying rate of 0.1 kg / hour. Alteration of the drying phase were in line to the shrinkage of areca nut weight, the largest weight loss occurs in the initial adjustment phase, which was 12% in the 3rd hour drying time period. In the initial adjustment phase, the outer shell (epicarp) begins to shrivel, the color of the skin turns brownish, the seed (endocarp) begins to detach from the coir layer (mesocarp), the color of the seed is still normal. In the phase of a constant rate of outer skin color getting darker and duller, seeds begin to crack due to reduced moisture content. In the phase of decreasing the seed layer separated from the coir layer gets bigger, the cracks in the seeds increase, the white fibers in the seeds turn black.